KEJAHATAN LINGKUNGAN: SUATU TINJAUAN KRIMINOLOGIS - Dermawan, Mohammad Kemal (Jurnal Masyarakat dan Budaya, 2025)
At their best, corporations can be a force for good in society, developing new technologies, promoting education and training and providing quality jobs. However, too often businesses have made their profits at the expense of the poorest people around the world, and at a huge cost to the environment. There must be some increasing attention on corporate social responsibility – the integration of social, environmental and governance concerns into business operations. Kata Kunci: Korporasi, Kejahatan Lingkungan, White Collar Crime, Reaksi Sosial dan Kontrol Sosial